Methods to align program system requirements with enterprise strategy and infrastructure - Paškevičiūtė, Lina; Čaplinskas, Albertas (Lietuvos matematikos rinkinys, 2021)
The paper addresses the problem of achieving alignment of information system requirements and business strategy and infrastructure. Themost popular strategic alignmentmodels and enterprise architecture frameworks are reviewed. The role of these models and frameworks in the process of requirements definition and the ways to utilize them to achieve the alignment are analyzed.